2001
DOI: 10.1101/gr.169101
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Analysis of Human Disease-Associated Gene Sequences In Drosophila melanogaster

Abstract: We performed a systematic BLAST analysis of 929 human disease gene entries associated with at least one mutant allele in the Online Mendelian Inheritance in Man (OMIM) database against the recently completed genome sequence of Drosophila melanogaster. The results of this search have been formatted as an updateable and searchable on-line database called Homophila. Our analysis identified 714 distinct human disease genes (77% of disease genes searched) matching 548 unique Drosophila sequences, which we have summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
533
1
14

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 840 publications
(550 citation statements)
references
References 13 publications
2
533
1
14
Order By: Relevance
“…In a recent comparative sequence analysis of nearly 300 molecularly identified human MR genes, we found that 87% have a highly similar relative in Drosophila [Inlow and Restifo, 2004]. This percentage is higher than previous reports that used the same sequence-similarity criteria to compare Drosophila genes and human disease genes of diverse types [Fortini et al, 2000;Reiter et al, 2001]. Furthermore, the extent and type of amino acid sequence similarity between the human MR genes and their fruit fly counterparts were sufficient in 76% to suggest that they have similar biological functions in the two species [Inlow and Restifo, 2004].…”
Section: Rationale For Studying Mr In Drosophilacontrasting
confidence: 60%
“…In a recent comparative sequence analysis of nearly 300 molecularly identified human MR genes, we found that 87% have a highly similar relative in Drosophila [Inlow and Restifo, 2004]. This percentage is higher than previous reports that used the same sequence-similarity criteria to compare Drosophila genes and human disease genes of diverse types [Fortini et al, 2000;Reiter et al, 2001]. Furthermore, the extent and type of amino acid sequence similarity between the human MR genes and their fruit fly counterparts were sufficient in 76% to suggest that they have similar biological functions in the two species [Inlow and Restifo, 2004].…”
Section: Rationale For Studying Mr In Drosophilacontrasting
confidence: 60%
“…In addition, several signaling systems have been implicated in axonal pathfinding and synapse formation, including by the Netrin, Round About (Robo), Semaphorin, Neuroglian, and BMP-mediated pathways. Diseasecausing mutations have been identified in components of nearly all of these major signaling pathway categories (Reiter et al, 2001). Consistent with the high degree of evolutionary conservation between vertebrate and invertebrate genetic systems, many human diseases associated with mutations in signal-transduction pathways lead to developmental disorders, as illustrated by the diseases covered in this volume.…”
Section: Conserved Signaling Pathways In Vertebrates and Invertebratementioning
confidence: 71%
“…In the course of discussing these points, we review the compelling evidence that developmentally important genes have been phylogenetically conserved and the likelihood that developmental disorders in humans will often involve genes controlling similar morphogenetic processes in vertebrates and invertebrates. A systematic analysis of human disease gene homologs in Drosophila supports this view since 75% of human disease genes are structurally related to genes present in Drosophila and more than a third of these human genes are highly related to their fruit fly counterparts (Bernards and Hariharan, 2001;Reiter et al, 2001;Chien et al, 2002).…”
Section: Ethan Bier and William Mcginnismentioning
confidence: 90%
See 2 more Smart Citations